2014
DOI: 10.1111/pcmr.12298
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics regulate melanogenesis through proteasomal degradation of MITF via ROSERK activation

Abstract: Mitochondrial dynamics control mitochondrial functions as well as their morphology. However, the role of mitochondrial dynamics in melanogenesis is largely unknown. Here, we show that mitochondrial dynamics regulate melanogenesis by modulating the ROS-ERK signaling pathway. Genetic and chemical inhibition of Drp1, a mitochondrial fission protein, increased melanin production and mitochondrial elongation in melanocytes and melanoma cells. In contrast, down-regulation of OPA1, a mitochondria fusion regulator, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 48 publications
5
42
0
1
Order By: Relevance
“…It is known that Mitf expression is regulated by MAPK signaling [45], and we therefore focused on this pathway. Intriguingly, there is evidence suggesting that the MAPK pathway can be influenced by copper, through the finding that copper can enhance the MEK1/2-dependent phosphorylation of ERK1/2, leading to enhanced proteasomal degradation of Mitf [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Mitf expression is regulated by MAPK signaling [45], and we therefore focused on this pathway. Intriguingly, there is evidence suggesting that the MAPK pathway can be influenced by copper, through the finding that copper can enhance the MEK1/2-dependent phosphorylation of ERK1/2, leading to enhanced proteasomal degradation of Mitf [37].…”
Section: Discussionmentioning
confidence: 99%
“…Microphthalmia transcription factor specifically binds to the M‐box and E‐box motifs of Tyr , TRP1 , and TRP2 and upregulates their expression (Bertolotto et al ., ). Our results showed an increase in the expression of MITF upon Sak treatment and reach its maximum after 24 h. Studies have shown that the MAP kinases signaling pathways (ERK, JNK, and p38) are involved in the regulation of MITF activity (Bu et al ., ; Ye et al ., ; Kim et al ., ). Activation of ERK MAP kinases induces the phosphorylation of MITF at Ser 73, and together with recruitment of the transcriptional coactivator p300, this process leads to ubiquitination and proteasome‐mediated degradation of MITF.…”
Section: Discussionmentioning
confidence: 97%
“…As expected, our results showed that MTFP1 significantly increased the phosphorylation of DRP1 at Ser616, while decreased the phosphorylation of DRP1 at Ser637, which subsequently facilitated the fragmentation of mitochondrial in OSCC cells. A body of evidence has indicated the association between increased mitochondria fission and production of ROS (Kim et al, ; Wang et al, ; Huang et al, ), which contributes to tumor cell growth by inducing genomic instability and participating in signaling pathways (Yang et al, ; de Sa Junior et al, ; Prasad et al, ; Moloney and Cotter, ). Our results showed a dramatic induction of ROS production and activation of Akt signaling by MTFP1 in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%